Subjective wellbeing: why weather matters - Feddersen, John; Metcalfe, Robert; Wooden, Mark (Journal of the Royal Statistical Society. Series A, Statistics in society, 2016)
The paper reports results from the first ever study of the effect of short-term weather and long-term climate on self-reported life satisfaction that uses longitudinal data. We find robust evidence that day-to-day weather variation impacts self-reported life satisfaction. Utilizing two sources of variation in the cognitive complexity of satisfaction questions, we present evidence that weather effects arise because of the cognitive challenge of reporting life satisfaction. We do not detect a relationship between long-term climate and self-reported life satisfaction by using an individual fixed effects specification, which identifies climate impacts through individuals moving location.